Improvements in thermal conductivity and mechanical properties of HDPE/nano‐SiC composites by the synergetic effect of extensional deformation and ISBS. Issue 24 (21st February 2019) - Xiaochun, Yin; Yang, Li; Di, Cheng; Yanhong, Feng; Guangjian, He
ABSTRACT: A new melt blending method under synergy of extensional deformation and in‐situ bubble stretching for high‐density polyethylene (HDPE) thermally conductive composites filled by nano silicon carbide (nano‐SiC) was reported. Effects of loadings and mixing time of azodicarbonamide (AC) foaming agent on the properties of the composites were experimentally studied. Scanning electron microscopy imaging showed that the nano‐SiC particles dispersed uniformly in the HDPE matrix with the addition of AC. The complex viscosity and storage modulus increased with increasing AC content and decreased with increasing mixing time. The mechanical properties of the composites improved with the addition of AC and proper mixing times. The thermal conductivity of the composites increased from 0.2 to 0.7 W m −1 K −1 without any damage to the mechanical properties when the mixing time increased from 2 to 6 min. These results showed that the new mixing technique enables us to prepare particle‐filled thermally conductive polymer composites. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47648. Abstract :